2007
DOI: 10.1002/14651858.cd002869.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Individual or group antenatal education for childbirth or parenthood, or both

Abstract: Analysis 4.1. Comparison 4 Expanded childbirth education classes versus traditional childbirth education classes, Outcome 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
294
1
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(313 citation statements)
references
References 87 publications
6
294
1
12
Order By: Relevance
“…Van der Gucht and Lewis (2015) identify how the acceptance of labour pain is a crucial coping strategy for women. All authors suggest more research is needed in this area (see also Gagnon and Sandall, 2007), and our findings support this.…”
Section: Women's Views On Pharmacological Pain Relief For Laboursupporting
confidence: 83%
See 1 more Smart Citation
“…Van der Gucht and Lewis (2015) identify how the acceptance of labour pain is a crucial coping strategy for women. All authors suggest more research is needed in this area (see also Gagnon and Sandall, 2007), and our findings support this.…”
Section: Women's Views On Pharmacological Pain Relief For Laboursupporting
confidence: 83%
“…Foucault (1991, p. 75) identifies that power can be observed in 'regimes of practice'; daily interactions and occurrences are where dominant discourses are recreated. What this means is that at every interaction, individuals have the potential to contribute to or disrupt systems of power (Foucault, 2008). For example, in line with the need to provide information about alternative options within the informed consent framework, when discussing epidural analgesia it would fit well within their professional remit for midwives to not only inform women of the risks and benefits, but also mention that use of water in labour significantly reduces the need for epidural analgesia (Cluett and Burns, 2009) or that women who use epidural analgesia are more likely to remember the pain of labour prior to its insertion than women who use no pain relief due to its effect on oxytocin levels (Uvnäs Moberg, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies from Zimbabwe, Nepal and Tanzania, report that less than three minutes are spent on individual counseling per consultation in antenatal clinics. 13,16,17 With the simulation of focus antenatal care (FANC) in Ghana by the Ghana health Service it looks like not much has changed yet from the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the program may vary, from smaller groups to bigger classes. Although education programs for childbirth and/or parenthood are abundant and attended by a large percentage of pregnant women worldwide, their effects on knowledge, anxiety, sense of control, labor and birth support, pain, breastfeeding, infant-care abilities, and psychological and social adjustment still remain largely unknown (Gagnon & Sandall, 2008). In a Swedish cohort study, researchers found that participation in PEC during pregnancy did not seem to affect first-time mothers' experience of childbirth and assessment of parental skills (Fabian, Rådestad, & Waldenström, 2005).…”
Section: Introductionmentioning
confidence: 99%